Business network management theories and issues - Lindfors, Sini (2011)
Lindfors, Sini Business network management theories and issues Jyväskylä: University of Jyväskylä, 2010, 27 p. Computer systems science, bachelor thesis Supervisor: Seppänen, Ville The essay discusses management of business networks by researching existing literature and the objective is to discover how to manage business networks. The network term is defined and various theories of business network man-agement are presented and findings discussed. The results are general in nature as the management of business networks is rather new field in scientific re-search. The three managerial paradoxes present the forces controlling the busi-ness network and they highlight the importance of thinking out of the box. The strategizing offers different dimensions of strategic resources in the network and the model of managing in the network has three basic elements to help to understand business networks. All presented theories are very interesting but they do not succeed in offering any practical details. However, they do present a general understanding of business networks, which is important in order to be able to operate and maintain in these. There is a high demand for more re-search and findings.